Evaluation of Risks of Bias in Addiction Medicine Randomized Controlled Trials. (18th August 2020) - Wayant, Cole; Tritz, Daniel; Horn, Jarryd; Crow, Matt; Vassar, Matt
Abstract: Aims: Perhaps the most important step when designing and conducting randomized controlled trials (RCTs) in addiction is to put methodological safeguards in place to minimize the likelihood for bias to affect trial outcomes. In this study, we applied the revised Cochrane risk of bias tool (ROB 2) to RCTs of drug, alcohol or tobacco interventions. Methods: We searched for trials published in 15 addiction medicine journals over a 7-year period. Our primary endpoint is the risk of bias of included studies. We conducted a sensitivity analysis of publicly funded trials. Results: Overall, included RCTs were most often at high risk of bias per our judgments (244/487, 50.1%). However, significant proportions of included RCTs were at low risk of bias (123/487, 25.3%) or some concerns for bias (120/497, 24.6%). RCTs with behavioral modification interventions (19/44, 43.2%) and alcohol interventions (80/150, 53.3%) had the highest proportion of high-risk judgments. In a sensitivity analysis of publicly funded RCTs), 195/386 (50.5%) were at high risk of bias. Conclusions: Approximately half of included drug, alcohol or tobacco RCTs in our sample were judged to be at high risk of bias with the most common reason being a lack of proper blinding or proper description of blinding. Key action items to reduce bias in future addiction RCTs include adequate randomization, blinding and inclusion of a trial registry number and protocol.